Analisis Perbandingan Kinerja Pola MVVM dan MVP pada Sistem Dasbor Android - Fajar Pradana; Raziqa Izza Langundi; Djoko Pramono; Nur Ida Iriani (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2025)
The rapid growth of the Android market in various developing countries has driven the demand for higher-quality applications. Developing Android-based applications presents specific challenges, such as the need for responsive designs and optimization for devices with diverse specifications. Design patterns like model-view-controller (MVC), model-view-presenter (MVP), and model-view-viewmodel (MVVM) have become popular approaches to address these issues. However, studies on the performance of design patterns in Android applications, especially in modern programming languages like Kotlin, remain limited. This research aims to compare the performance of the MVP and MVVM design patterns in an Android-based boarding house management application, KosGX. This application utilized Kotlin and featured an interactive dashboard requiring significant device resources. Testing was conducted by measuring performance across three key aspects: central processing unit (CPU) usage, memory usage, and system response time. The results of the study showed that MVVM outperformed in CPU efficiency, with an average usage of 8.92% compared to 11.15% for MVP. In terms of memory usage, MVVM was also slightly more efficient, with an average usage of 121.48 MB compared to 121.55 MB for MVP. However, MVP excelled in response time, averaging 236.88 ms, whereas MVVM reached 252.68 ms. This study underscores that the choice of design pattern affects application performance. MVVM is more efficient in CPU and memory usage, while MVP offers better response times. These findings provide valuable insights for developers in selecting the optimal design pattern based on the specific needs of their applications.